1983
DOI: 10.1071/mf9830441
|View full text |Cite
|
Sign up to set email alerts
|

Fish of channelized and unchannelized sections of the Bunyip River, Victoria

Abstract: The distribution and abundance of fish at three channelized and three unchannelized sites on the Bunyip River in southern Victoria were investigated. Ten species of native fish, including the Australian grayling (Prototroctes maraena), and two species of introduced fish were collected in three sets of seasonal samples by electrofishing. The unchannelized sites and a channelized site directly above a small weir had significantly higher species richness, total fish biomass, numerical density and standing crop (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Bramblett & Fausch (1991) Sites with highest levels o relative biotic integrity consistently had woody debris densities between about 5000 and 20 000 m 2 km -2 , but woody debris was scarce (0 to 1000 m2 km -2) at sites with lowest relative IBI (Table 9) . Large woody debris is an important structural component o warmwater ish habitats (Hickman, 1975, Hortle & Lake, 1983, Angermeier & Karr, 1984 . In sandy warmwater streams, woody debris may be the locus or much o the invertebrate production (Benke et al, 1985) and create higher levels o physical heterogeneity (Shields & Smith, 1992) and pool availability (Ebert et al ., 1991) .…”
Section: Discussionmentioning
confidence: 99%
“…Bramblett & Fausch (1991) Sites with highest levels o relative biotic integrity consistently had woody debris densities between about 5000 and 20 000 m 2 km -2 , but woody debris was scarce (0 to 1000 m2 km -2) at sites with lowest relative IBI (Table 9) . Large woody debris is an important structural component o warmwater ish habitats (Hickman, 1975, Hortle & Lake, 1983, Angermeier & Karr, 1984 . In sandy warmwater streams, woody debris may be the locus or much o the invertebrate production (Benke et al, 1985) and create higher levels o physical heterogeneity (Shields & Smith, 1992) and pool availability (Ebert et al ., 1991) .…”
Section: Discussionmentioning
confidence: 99%
“…Where documented, the impacts of desnagging have included extensive erosion of the bed and banks (Erskine and Webb, 2003;Brooks et al, 2004), significant increases in channel capacity (Webb and Erskine, 2003;Brooks et al, 2004) and a loss of diversity in the channel and velocity profiles (Shields and Smith, 1992;Kail, 2003). The presence of wood in a channel, however, has been shown to alter local flow and depositional patterns, increasing the structural diversity of the channel (Hortle and Lake, 1983;Harmon et al, 1986;O'Connor, 1991).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, Whelan et al (1981) found species diversity to differ only slightly between channelized and unaltered streams, but instead found evenness was less in channelized streams. Numerous other studies report reductions in fish growth, condition, biomass, density, and diversity following channelization because of alterations to habitat variables such as sinuosity, gradient, flow, substrate type, pool-riffle periodicity, structure (rocks and large woody deposits), riparian vegetation, backwater, and water quality variables (Congdon, 1971;Tarplee et al, 1971; Arner et al, 1975;Bulkley et al, 1976;Groen and Schmulbach, 1978;Hortle and Lake, 1983;Edwards et al, 1984;Portt et al, 1986;Brookes, 1988;Hubbard et al, 1993;Punchard et al, 2000). These gradients interact to affect the stream fauna and assigning more importance to one relative to others is difficult, although changes in physical variables appear to have greater effects than water quality measures (Brookes, 1988).…”
Section: Assemblage Structurementioning
confidence: 95%
“…Evaluation of these techniques has been conducted to some extent. Hortle and Lake (1983) found a small weir at a channelized site increased fish species richness and biomass. Edwards et al (1984) reported that the creation of riffle and pool habitat via the installation of artificial weirs benefited game and non-game species.…”
Section: Assemblage Structurementioning
confidence: 98%